Propuesta metodológica “Modelo pedagógico hoslístico” y su influencia del desarrollo del pensamiento resolutivo en estudiantes del 1er grado de secundaria de la I.E Manuel Segundo del Águila - Reátegui Linarez, Llina Karen (2011)
Proposed research methodology called "Holistic Teaching Model" and its influence on the development of Thought Resolving high school students in the district of Rioja, emerged from the holistic learning perspective which is to provide students with the tools to learn the set, an integrated and thus develop their learning potential. In this sense, the objective proposed in the research involved determining the influence of the proposed methodology in resolving the development of thinking of students in the first grade of secondary education since the area of Science Technology and Environment. Also, because the background was assumed that this influence would be significant this was the research hypothesis for this study. In the methodological part, under a quasi-experimental design, we considered two groups: a pilot who applied the proposal and a control group whose purpose was comparison was therefore not subject to the proposed methodology. Under these conditions, each group consisted of a sample of 28 students. T o obtain the results was necessary to design and implement a pre and post test consisting of the same 1 O items to mea su re the resolving of the students thought, which is considered one ítem for each specifíc capacity. Result of the application of the instrument, the pickup, analysis and interpretation of data obtained from field work, with 95% confidence by Student t test for difference of means test was performed hypothesis and concluded that methodological proposal Holistic Teaching Model has significantly influenced the development of thought in resolving the first grade students of secondary education in the area of Science, Technology and Environment of School "Manuel Velasquez Second Eagle" (PONASAPA) of Rioja district.